miR-1 Mediated AMPK Pathway on Cardiomyocyte Apoptosis in Hypertensive Rats: miR-1 Mediated AMPK Pathway on Cardiomyocyte Apoptosis - Huang, Xiaoli; Wang, Jinlin (Cellular and Molecular Biology, 2022)
In recent years, it has been found that miRNA has a very close relationship with cardiovascular system diseases. Heart disease is accompanied by a change of the miRNA expression spectrum. Changing the expression of miRNA in or out of cells can cause heart diseases such as myocardial infarction, hypertrophy or arrhythmia. Mitogen-activated protein kinases (MAPKs) are important transmitters of cell surface signals to the nucleus. The family influences the biological responses of cells (e.g., proliferation, differentiation, transformation and apoptosis) by affecting the transcription and regulation of genes in animal cells. Based on the above background, the purpose of this study was to study the effect of the mir-1-mediated AMPK pathway on cardiomyocyte apoptosis in hypertensive rats. The expression level of miRNA-1 in cultured rat H9c2 cardiomyocytes was detected by real-time PCR to determine the success of the transfection. MTT method was used to detect the cell viability. Flow cytometry was used to detect the cell apoptosis, and real-time PCR and Western blot were used to detect the mRNA and protein expression of bcl-2. The results were compared with those of H9c2 cells (blank control group) and miRNA negative control fragments (negative control group). As an important kinase regulating energy homeostasis, AMPK is one of the central regulators of metabolism in eukaryotic cells and organisms, responsible for regulating cellular capacity input and output and maintaining the smooth functioning of cellular physiological activities. At the same time, AMPK is a key protein involved in a variety of signaling pathways. The results showed that the apoptosis rate of myocardial cells in the miRNA-1 group decreased (0.710 ± 0.009661)% vs (1.066667 ± 0.02603)% compared with that in the spontaneous hypertension control group (P < 0.001). The transfected miRNA-1mimics can up-regulate the expression of miRNA-1 in cells, inhibit the proliferation of cardiomyocytes and promote apoptosis.